Left atrial myxoma: Unusual presentation as a cystic tumor. Issue 2 (19th December 2019) - Ntinopoulos, Vasileios; Dushaj, Stak; Brugnetti, Daniele; Rings, Laura; Loeblein, Helen; Dzemali, Omer
Abstract: Myxomas are the most common cardiac tumors, benign, and usually located in the left atrium. Typically echocardiography reveals a solid tumor, whereas cystic myxomas are rare with only a few cases documented in the literature. We describe the case of a 63‐year‐old, female patient with an unusual presentation of a left atrial myxoma as a cystic tumor.